Superconductors containing phosphates groups derivatives from YBa2Cu3O7 - González, J. C. (2013)
We completed the characterization of the superconducting compound [Y1-xCax](BaSr)Cu3-y(PO4)y0zderivativesof YBa2Cu3O7, prepared in normal temperature and pressure conditions by solid state reaction,reported in our previous results. We will show the quantitative results obtained from the analysis by Rietveldmethod of the X-ray diffraction patterns and from magnetic susceptibility measurement in the superconductingregion.